A comparative study between magnetic resonance imaging and transvaginal sonography for evaluation of uterine fibroid using histopathology as a gold standard - Goyal, Alka; Mehta, Deeksha; Mangalhara, Naresh K.; Poonia, Sunita (International Journal of Research in Medical Sciences, 2020)
Background: Uterine fibroids constitute a substantial bulk of patients presenting to Gynaecology department. Many newer imaging modalities have evolved for their correct evaluation, but in a developing country like India, ultrasound is still being used as a screening as well as diagnostic modality. So, this study was done to compare ultrasound and magnetic resonance imaging for evaluation of uterine fibroids in terms of their sensitivity, specificity Trans vaginal and positive predictive value using Histopathology as a gold standard so as to improvise on current clinical practices in this country. Methods: An ethically approved prospective study was done upon 50 patients with suspected uterine masses at SMS Hospital Jaipur. All included patients underwent Trans vaginal Ultrasound (TVS) and Magnetic resonance imaging (MRI) and were accordingly treated surgically. Histopathology report was traced postoperatively. Data was collected and subjected to various statistical tests including Cohen’s kappa. Results: Most of the patients were <50 years and presented with complains of pain abdomen. Among total 50 cases, the sensitivity of TVS and MRI was 44% and 92%, specificity was 96% and 88%, PPV was 91.67% and 88.46%, NPV was 63.16% and 91.67% respectively, kappa was 0.40 and 0.80 i.e. agreement between TVS and MRI v/s HPE was 40% and 80% respectively. The diagonal agreement between transvaginal USG and MRI, was 63%. Conclusions: TVS is a good screening modality but MRI is definitely better for proper characterization and localization of fibroids enabling clinicians to select the most appropriate management in everyday clinical practice.